2001
DOI: 10.5558/tfc77519-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Armillaria root disease on succession in red pine plantations in southern Ontario

Abstract: Armillaria root disease created openings in southern Ontario red pine plantations that are gradually succeeding to hardwood-dominated mixedwoods through natural regeneration. A study of 13 root disease centres found several tree and shrub species colonizing the openings. Black cherry was the most important hardwood and white pine the most important conifer colonizer. Mortality of black cherry and white pine regeneration was greater than for other species. Long-term survival of conifers in the centres is doubtf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Over time, the forest cover provided by these plantations has improved soil conditions (Wilde 1964, Stone 1975, McPherson and Timmer 2002 and moderated the microenvironment of these once-exposed, degraded lands, creating understory conditions conducive to the natural establishment of more shade-tolerant forest tree species (Russell 1955, Truax et al 2000, McLaughlin 2001, Hewitt and Kellman 2002. Disturbance by thinning and the natural mortality of single or groups of trees in older plantations has stimulated the development of this forest understory and accelerated the succession of these plantations to a more natural forest composition (Young 1933, Russell 1955, Goldblum 1998, McLaughlin 2001, Parker et al 2001.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, the forest cover provided by these plantations has improved soil conditions (Wilde 1964, Stone 1975, McPherson and Timmer 2002 and moderated the microenvironment of these once-exposed, degraded lands, creating understory conditions conducive to the natural establishment of more shade-tolerant forest tree species (Russell 1955, Truax et al 2000, McLaughlin 2001, Hewitt and Kellman 2002. Disturbance by thinning and the natural mortality of single or groups of trees in older plantations has stimulated the development of this forest understory and accelerated the succession of these plantations to a more natural forest composition (Young 1933, Russell 1955, Goldblum 1998, McLaughlin 2001, Parker et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance by thinning and the natural mortality of single or groups of trees in older plantations has stimulated the development of this forest understory and accelerated the succession of these plantations to a more natural forest composition (Young 1933, Russell 1955, Goldblum 1998, McLaughlin 2001, Parker et al 2001. In younger plantations with little disturbance history, very low understory light and thick litter layers impede the establishment of understory vegetation (Russell 1955, Gysel 1966, Anderson et al 1969, Truax et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in harvest practices, natural forest succession, and weather patterns contributed to these changes, but most likely so did insect outbreaks and diseases, including Armillaria root disease. Evidence of the significance of A. ostoyae in forest succession and composition has been reported by McLaughlin (2001b) in areas of southern Ontario. Hardwood species are colonizing openings where A. ostoyae has killed the red pine.…”
Section: Resultsmentioning
confidence: 96%
“…Beginning in the late 1980s, USDA Forest Service personnel observed tree mortality and decline in some areas of the Chequamegon. Armillaria root disease, important in several areas of North America (Bruhn et al 2000, Lundquist 2000, Mallett and Maynard 1998, McLaughlin 2001b, Morrison et al 2001, Rizzo and Slaughter 2001, was suspected of contributing to these observed declines, but no mycological investigations had been done in this area.The objectives of this study were to identify the species of Armillaria present in the Chequamegon, especially in declining stands, and to relate these findings to previously collected information about Armillaria, particularly in the western Great Lakes States, but also in other areas of North America. This is the first step in assessing the role of these fungi in the Chequamegon forest.…”
mentioning
confidence: 99%
See 1 more Smart Citation